Quality Analysis of the Cyberlearning Application at SMAN 1 Air Saleh Using the McCall Method - Ilham Aji Saputra (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
This study aims to measure the software quality of the Cyberlearning Application at SMAN 1 Air Saleh. Following a comprehensive literature review, data were collected through questionnaires developed based on the McCall Method as a software quality assessment framework. The completed questionnaires were tested for validity and reliability to ensure that the variables and indicators were both valid and reliable. The respondents consisted of 82 students, comprising 18 students from Grade X, 15 students from Grade XI Science, 15 students from Grade XI Social Science, 19 students from Grade XII Science, and 15 students from Grade XII Social Science. The respondent profile included 41 male and 41 female students, with an age distribution of 16 respondents aged 15 years, 16 respondents aged 16 years, 31 respondents aged 17 years, 17 respondents aged 18 years, and 2 respondents aged 19 years. The validated variables and indicators were subsequently used to calculate the quality value (Fa) for each factor through a weighting process conducted by experts using a scale ranging from 0.1 to 0.5 for the factors of Correctness, Reliability, Efficiency, Integrity, and Usability. The McCall Method calculation results indicate that the Cyberlearning Application achieved quality scores of 63% for Correctness, 60.40% for Reliability, 78.20% for Efficiency, 78.40% for Integrity, and 70% for Usability. Based on these results, the Cyberlearning Application at SMAN 1 Air Saleh is classified as a high-quality application.